2012
DOI: 10.1177/0269215512460779
|View full text |Cite
|
Sign up to set email alerts
|

A 6-month follow-up after constraint-induced movement therapy with and without transfer package for patients with hemiparesis after stroke: a pilot quasi-randomized controlled trial

Abstract: Our results confirmed the long-term effects of the transfer package in constraint-induced movement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 13 publications
0
53
0
1
Order By: Relevance
“…13,62 Despite the varied intervention options, a significant percentage of individuals are unable to maintain and generalize the gains achieved in therapy to the natural environment after therapy ends. 6365 Although task-oriented training approaches highlight the importance of repetition and task specificity, they sometimes downplay the achievement of skilled movement in the service of functional tasks. Maladaptive or “bad use” may occur when less optimal, unskilled, solutions—ones that rely on compensatory strategies—are used.…”
Section: Infusing Contemporary Motor Learning Into Neurorehabilitatiomentioning
confidence: 99%
“…13,62 Despite the varied intervention options, a significant percentage of individuals are unable to maintain and generalize the gains achieved in therapy to the natural environment after therapy ends. 6365 Although task-oriented training approaches highlight the importance of repetition and task specificity, they sometimes downplay the achievement of skilled movement in the service of functional tasks. Maladaptive or “bad use” may occur when less optimal, unskilled, solutions—ones that rely on compensatory strategies—are used.…”
Section: Infusing Contemporary Motor Learning Into Neurorehabilitatiomentioning
confidence: 99%
“…This learned non-use phenomenon is responsible for increased weaknesses, decreased abilities of the paretic upper limb in performing unimanual and bimanual activities, and restricted social participation5 - 9. Therefore, the treatment of such residual deficits is critically important for the stroke population and Constraint-Induced Movement Therapy (CIMT) has emerged as a promising intervention to improve upper limb function after stroke10 , 11. …”
Section: Introductionmentioning
confidence: 99%
“…Some researchers consider the transfer package the most important component of CIMT. In fact, research has shown that usage of the affected arm in daily life is significantly different between patients treated with and without the transfer package component (16, 17). However, many therapists question whether CIMT could benefit their patients because of the shortage of sites possessing the clinical resources to provide the intervention for the long duration required for effectiveness (18).…”
Section: Introductionmentioning
confidence: 99%